Hubungan Pola Asuh Orang Tua dengan Kepercayaan Diri Remaja di SMK Borneo Lestari Banjarbaru - Saputri, Linda Kamelia; Lestari, Dhian Ririn; Zwagery, Rika Vira (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2020)
Self- confidence is a very important aspect in adolescent development. Self-confidence grows from theparenting environtment in the family. If adolescents had low self-confidence, then adolescents will havedifficulties in living life. The purpose of this study was to find out the relationship between parenting styles withadolescent self-confidence. This study used a correlational research method with a cross-sectional design. Theresearch included 87 adolescents in the SMK Borneo Lestari Banjarbaru. Subject selection with stratifiedrandom sampling technique. This research used a parenting styles questionnaire and a self-confidencequestionnaire with data analysis used spearman correlation test. The results showed that the majority ofparenting styles is democratic were 74 respondents (85.1%) and high self-confidence was 54 respondents(62.1%). The results of data analysis founded there is a relationship between parenting styles with adolescentself-confidence at SMK Borneo Lestari Banjarbaru (p-Value = 0.001, r = 0,343). These results showed aparent's approach to adolescents through appropriate parenting styles is very important for adolescentdevelopment, one of which is self-confidence. Adolescents will have good self-confidence if parents provideappropriate parenting styles.